Hubungan Motivasi Internal dan Eksternal Pemustaka terhadap Pemanfaatan Layanan Referensi di UPT. Perpustakaan Universitas Negeri Padang - Husnika, Maulida; Nurizzati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted with the aim to find out the relationship between internal and external motivation of library users to the utilization of reference services, and whether there is a relationship between internal motivation and external motivation to the utilization of reference services Technical Implementation Unit of Padang State University Library. This research uses a quantitative approach with survey method. The sample in this study amounted to 100 respondents who were the whole of the population, because the population was not large. The sampling technique is using accidental sampling. The results showed that internal and external motivation had a positive and significant effect on the utilization of reference services, external motivation had a greater influence with a regression coefficient value of 0.522 and a beta value of 0.448. The R-square (R2) value is 0.632 which means that internal and external motivation has a 63.2% relationship to the utilization of reference services and 36.8% is explained by other factors. This study concludes that internal motivation (desire to succeed, needs, and future goals) can encourage the utilization of reference services by visitors, and recommends that external influences (external motivation) can increase the utilization of reference services at Technical Implementation Unit of Padang State University Library.